Characterization and transcriptional analysis of the promoter region of the Duffy blood group, chemokine receptor (DARC) gene in cattle - Carvalho, T. L. [UNESP]; Ribolla, P. E. M. [UNESP]; Curi, Rogerio Abdallah [UNESP]; Mota, L. S. L. S. [UNESP] (Elsevier B.V., 2009)
The Duffy antigen is the only receptor for Plasmodium vivax, a hemoparasite of the phylum Apicomplexa and the cause of vivax malaria in humans. Resistance to this parasite in the majority of black African individuals and their descendents is due to a mutation in the gene promoter region, which blocks its transcription on erythrocytes. Regarding bovine babesiosis, it is known that taurine breeds are more susceptible to parasite infection than zebuine breeds. In order to verify whether the same human resistance occurs in bovine, the 5' flanking region of the DARC gene was isolated and characterized in Bos indicus and Bos taurus. Four single nucleotide polymorphisms were identified and genotyped (SNP1: EF_647729.1:g.91 C > T; SNP2: EF_647729.1:g.405C > T; SNP3: EF_647729.1: g.433A > G and SNP4: EF_647729.1:g.588A > G), which showed significant frequency differences among 99 bovines of each species (n = 198). Characterization of the isolated region revealed the presence of 6 putative haplotypes, 14 genotypes, which are formed by haplotypes, and numerous putative transcription factor binding sites. Only the thymine presence on SNPs 1 and 2, more common in B. indicus, was observed to alter some of the sites in this region. Despite this fact, analyses through real-time PCR on bovines that present the most common homozygote genotypes of each species, which contrast for all the polymorphism, revealed no difference on the DARC gene transcription. Thus, in principle, it was concluded that the polymorphisms identified would not be useful as molecular markers in an improvement program for resistance to babesiosis. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Babesiosis; Bovine; SNPs; Polymorphisms